Introduction to Microsoft Lync 2013 - Bushong, Bill.; Safari eBooks ([Boston, MA?] : CompuWorks, 2013)
"This course shows students how to use the Microsoft powerful, all-in-one communication tool: Lync. Over the course of this video, students will understand how to use the interface, manage contacts, and set important defaults. Additional time will be spent learning how to communicate via instant message, email, audio or video calls, and live online meetings. Students will also learn more about Lync's seamless integration with Microsoft Office."--Resource description page.
Title from resource description page (viewed August 27, 2013).
Presenter, Bill Bushong.
Keywords: Microsoft Lync server; Client/server computing; Real-time data processing; Electronic books